Diffusion-weighted MRI of the spinal cord in cervical spondylotic myelopathy after instrumented fusion - Koch, Kevin M.; Nencka, Andrew S.; Klein, Andrew; Wang, Marjorie; Kurpad, Shekar; Vedantam, Aditya; Budde, Matthew (Frontiers in Neurology, 2023)
This study investigated tissue diffusion properties within the spinal cord of individuals treated for cervical spondylotic myelopathy (CSM) using post-decompression stabilization hardware. While previous research has indicated the potential of diffusion-weighted MRI (DW-MRI) markers of CSM, the metallic implants often used to stabilize the decompressed spine hamper conventional DW-MRI. Utilizing recent developments in DW-MRI metal-artifact suppression technologies, imaging data was acquired from 38 CSM study participants who had undergone instrumented fusion, as well as asymptomatic (non-instrumented) control participants. Apparent diffusion coefficients were determined in axial slice sections and split into four categories: a) instrumented levels, b) non-instrumented CSM levels, c) adjacent-segment (to instrumentation) CSM levels, and d) non-instrumented control levels. Multi-linear regression models accounting for age, sex, and body mass index were used to investigate ADC measures within each category. Furthermore, the cord diffusivity within CSM subjects was correlated with symptom scores and the duration since fusion procedures. The findings of the study provided evidence that the presence of fusion instrumentation results in consistent reductions in diffusivity.